Biomaterials : diverse application - Seguin, Ralph, editor (New York, NY : NY Research Press, 2015)
This book is a collection of reviews and original researches by experts and scientists regarding the field of biomaterials, its development and applications. It offers readers the potentials of distinct synthetic and engineered biomaterials. This book gives a comprehensive summary of the applications of various biomaterials, along with the techniques required for designing, developing and characterizing these biomaterials without any intervention by any industrial source. The researches and reviews focus on the functions of novel and familiar macromolecular compounds in nanotechnology and nanomedicine. The book also elucidates the chemical and mechanical modeling of these compounds so as to serve biomedical needs.